Effectiveness of Entomopathogenic Fungi Against Adult Red Flour Beetles (Tribolium castaneum) (Coleoptera: Tenebrionidae): Efektivitas Jamur Entomopatogen Terhadap Kumbang Tepung Merah Dewasa (Tribolium castaneum) (Coleoptera: Tenebrionidae) - Falhy, Majida Mohammad Abid; Azeez, Zahraa Falah (Universitas Muhammadiyah Sidoarjo, 2024)
The current study aimed to isolate some insect pathogenic fungi from the soil of wheat crops in different areas and test their effects on the adult stages of the red flour beetle Tribolium castaneum. Five species of fungi naturally infecting the flour beetle were recorded, and these genera were Beauveria bassiana and Metarhizium anisopliae, identified morphologically. Five local strains of insect pathogenic fungi were isolated, based on their macroscopic and microscopic characteristics. The concentrations of fungal spore suspensions affected the adults of the studied insect, with Beauveria bassiana being the most effective. The mortality rate of adults reached 93.33% when the highest concentration of the fungal suspension (17x108) was used after 10 days of treatment, while the mortality rate was 86.67% when using the suspension of Metarhizium anisopliae at the same concentration. One strain matched the species B. bassiana and four strains matched M. anisopliae. The identity of the strains was confirmed by amplifying and sequencing the ITS5-ITS4 region, and comparing the sequences to molecular databases and phylogenetic analyses. 99% identity values ​​were recorded with B. bassiana and M. anisopliae strains in molecular databases. Phylogenetic analyses confirmed that the sequences extracted from these strains fall within the group containing the reference sequences of B. bassiana and M. anisopliae, respectively, in the database. These results contribute significantly to the understanding of entomopathogenic fungi, which will aid in the development of biotechnological products in the field of biological control. Highlights: Soil fungi Beauveria bassiana and Metarhizium anisopliae infect red flour beetles. Fungal spore suspensions showed high mortality rates in beetle adults. Molecular analyses confirmed strains' identity, supporting biological control development. Keywords: Tribolium castaneum, entomopathogenic fungi, Beauveria bassiana. Metarhizium anisopliae. identification, contact toxicity